2023
DOI: 10.1101/2023.09.19.558449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mixed representations of sound and action in the auditory midbrain

GL Quass,
MM Rogalla,
AN Ford
et al.

Abstract: Linking sensory input and its consequences is a fundamental brain operation. Accordingly, neural activity of neo-cortical and limbic systems often reflects dynamic combinations of sensory and behaviorally relevant variables, and these mixed representations are suggested to be important for perception, learning, and plasticity. However, the extent to which such integrative computations might occur in brain regions upstream of the forebrain is less clear. Here, we conduct cellular-resolution 2-photon Ca2+ imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…Our recordings from corticorecipient neurons in the IC are consistent with previous studies demonstrating that neural representations of behavioral variables can be found in the auditory midbrain (Ruth et al, 1974;Nienhuis and Olds, 1978;Metzger et al, 2006;Gruters and Groh, 2012;Chen and Song, 2019;Yang et al, 2020;Saderi et al, 2021, Franceschi andBarkat, 2021;Shaheen et al, 2021;Quass et al, 2023). In keeping with responses recorded in the auditory cortex (Francis et al, 2018;Franceschi et al, 2021) and IC (Chen and Song 2019;Yang et al, 2020;Franceschi et al, 2021) of behaving mice, we found that the activity of most neurons was facilitated and about a third were suppressed during the sound detection task.…”
Section: Inferior Colliculus Neurons Exhibit Task-related Activitysupporting
confidence: 91%
“…Our recordings from corticorecipient neurons in the IC are consistent with previous studies demonstrating that neural representations of behavioral variables can be found in the auditory midbrain (Ruth et al, 1974;Nienhuis and Olds, 1978;Metzger et al, 2006;Gruters and Groh, 2012;Chen and Song, 2019;Yang et al, 2020;Saderi et al, 2021, Franceschi andBarkat, 2021;Shaheen et al, 2021;Quass et al, 2023). In keeping with responses recorded in the auditory cortex (Francis et al, 2018;Franceschi et al, 2021) and IC (Chen and Song 2019;Yang et al, 2020;Franceschi et al, 2021) of behaving mice, we found that the activity of most neurons was facilitated and about a third were suppressed during the sound detection task.…”
Section: Inferior Colliculus Neurons Exhibit Task-related Activitysupporting
confidence: 91%
“…Non-auditory activity is also abundant in the IC of awake animals (Metzger et al, 2006;Yang et al, 2020;Shaheen et al, 2021;Quass et al, 2023), and seemingly persists in absence of corticofugal feedback (Lee et al, 2023). Thus it is currently unclear if non-auditory activity in corticofugal neurons is the cause, or rather the consequence of similar activity patterns in IC neurons.…”
Section: Dendritic Ca 2+ Spikes As Effectors Of Supervised Plasticitymentioning
confidence: 99%
“…Movement and expectation influence neural processing across many stages of the auditory pathway, from the ear to the cerebral cortex 11,33 . For example, sound-evoked responses are suppressed in the auditory thalamus during behavior 16 , movement-related signals are present in the inferior colliculus 34,35 , and self-generated sounds are suppressed as early as the dorsal cochlear nucleus (DCN) 13 . The presence of movement-related signals along the auditory neuroaxis has raised the question of where along this pathway prediction-related signals arise.…”
Section: Discussionmentioning
confidence: 99%